COVID-19 and Liver Surgery: How the Pandemic Affected an Italian Medium-Volume HBP Center - Carissimi, Francesca; Scotti, Mauro Alessandro; Ciulli, Cristina; Fogliati, Alessandro; Uggeri, Fabio; Chiarelli, Marco; Braga, Marco; Romano, Fabrizio; Garancini, Mattia (Frontiers in Surgery, 2022)
Introduction While the COVID-19 pandemic is still ongoing, it is even more evident that victims of the pandemic are not only those who contract the virus, but also the countless patients suffering from other serious diseases (i.e., tumor) who have undergone delayed potentially life-saving surgery due to a lack of beds. Like many hospitals, ours also initially blocked all elective oncologic surgery, but these operations were “recovered” and reintegrated in a relatively short time, thanks to the establishment of COVID-free wards and operating rooms with staff dedicated to oncological surgery. In tis context, our aim is to assess whether and how the severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) pandemic has impacted our hepatobiliary surgery unit. Methods From our prospective database, we retrospectively took data from patients undergoing liver surgery in 2018–2019 (pre-COVID) and 2020–2021 (COVID period). Patients admitted to COVID-free wards must necessarily have a negative nasal swab from the previous 24 h. Results Between January 1, 2018, and December 31, 2019 (Group 1), 101 patients were treated; during the pandemic [January 1, 2020, and December 31, 2021 (Group 2)], 126 patients were treated. There was no statistical difference between the groups. The median postoperative hospital stay was 7 days for both groups; 7 patients had major complications (Clavien-Dindo > 3) in Group 1 and 11 in Group 2 (p = 0.795). A total of 4 patients died in Group 1 and 6 during the pandemic (p = 0.754). Tumor burden was significantly greater in Group 2 where nodule size, lymphadenectomy, and extrahepatic disease were significantly greater (p = 0.011, p = 0.004, and p = 0.026, respectively). Conclusion During the COVID pandemic, our HPB unit managed to offer a volume of tertiary-center hepatobiliary surgery without a significant impact in terms of length of stay, morbidity, or mortality despite the increase in tumor burden during the pandemic years.